O papel da música na formação integral de adolescentes: o violino como instrumento mobilizador de aprendizagens às camadas populares do municípios de Erechim/RS - Machado, Juliana (2018)
The entitled work “The music’s role in the full-time formation of teenagers: the violin as a mobilizing instrument of learning for the popular layer of the municipality of Erechim/RS” exposes the musical education theme, which objective is to analyze the contributions of violin teaching to the full-time formation of adolescents who are part of the Project “Orchestrating talents”, from Orquestra de Concertos de Erechim, RS. As a result of a qualitative bibliographical and exploratory research, associated to the field research, the study aims at the identification of social interactions, values and meanings of the violin study. The methodological course relies on bibliographical research related to full-time education, musical education and popular education. Similarly, semi-structured interviews, aiming to seek the necessary subsidies to answer the project’s problematic corresponding to the importance of violin study to the integral formation of the subjects, are conducted with violin students, teenagers, that belong to the age group that ranges from 12 to 14 years of age, attending the final years of Middle School, alongside parents, teachers and the project’s teacher, who configure the subjects of the exploratory research. The data collected in this research is analyzed systematically in pre-defined categories. Based on the assumption that society still does not value, with effect, music school education, due to cultural issues or lack of clarification, the deepening of questions related to it becomes essential in order to contribute with reflections that can clarify conceptions and mobilize actions in favor of musical education in the school context. Violin learning requires a lot of practicing, but despite that, the practice favors the development of motor coordination, auditory perception, expressivity, logical reasoning, and beyond that, discipline and pleasure. In other words, it contributes to the full-time formation of teenagers, and may also arouse interest for the musical learning of the people in the community as a whole. The study’s outcome is the strengthening of the relevance of musical education in the school environment for an effective full-time formation of the students.